Financial deepening and economic growth in China : an empirical study of 1990-2006. - Ye, Yin. (2009)
China’s economic growth has been remarkable since the 1978 reforms. Along with the development in real sector, the financial industry in China also deepens significantly. This paper is dedicated to examine the relationship between financial deepening and economic growth by using panel data of 31 provinces and municipals in China during 1990-2006. The result reveals a robust positive impact of financial deepening, as proxied by total loans, household savings and total deposits, on GDP growth. Hence, the implication of this paper is that a high priority should be given to capital accumulation and financial development, if China is to sustain its fast pace growth and social improvement in the next decade.